HUBUNGAN TRADISI PENGHANGATAN ARANG DAN KONDISI FISIK RUMAH DENGAN KEJADIAN ISPA PADA IBU NIFAS DI DESA BERAMPU KECAMATAN BERAMPU KABUPATEN DAIRI TAHUN 2020 - Fithri Handayani Lubis; Jeli Krisyani Sihombing (JURNAL KESMAS DAN GIZI (JKG), 2021)
Charcoal warming tradition is believed to help the recovery process in postpartum mothers. The purpose of this study was to determine the relationship between charcoal warming traditions and physical conditions of the house with the incidence of acute respiratory infections in postpartum mothers. The method of reseaech used the analytic case control approach. The population of this research was 50 mothers who had history of acute respiratory infections in Berampu village and the control sample was 50 people. The technique of the sample of this research is probability sampling.The Statistical analysis used bivariate analysis with chi square test and multivariate analysis with logistic regression test. The results of the bivariate analysis showed a relationship between the Charcoal Warming Tradition, p value = 0.002, between maternal parity, p value = 0.043, between the physical conditions of the house, p = 0.027, and the incidence of acute respiratory infections. The results of the multivariate analysis show that there is an influence between the Charcoal Warming Tradition (Exp B: 3,626), Mother Parity (Exp B: 2,517) and the Physical Condition of the House (Exp B: 2,354) on the incidence of acute respiratory infections in post- partum mothers in Berampu Village, District, Dairi Regency in 2020 The Suggestions for researchers Furthermore, this research is used as reference material regarding acute respiratory infections in order to carry out the proper management of acute respiratory infections. or Respondents to replace the warming tradition by using blankets. For public health center Developing health promotion for postpartum education.